Ceramic electronic component and method for manufacturing the same
By adding rare earth elements to the side edges of ceramic electronic components to promote sintering and controlling the amount of rare earth elements in the capacitor part, the problem of fast sintering speed in the capacitor part leads to delayed densification of the side edges is solved, and the reliability and moisture resistance of the components are improved .
Patent Information
- Application Number
- CN202110205937.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-28
- Filing Date
- 2021-02-24
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2041-02-24
AI Technical Summary
In ceramic electronic devices with high stacking density, the sintering speed of the capacitor portion is faster than that of the side edge, resulting in a delay in densification of the side edge, reducing the life characteristics and humidity resistance at high temperatures.
By adding rare earth elements to the side edges, especially selecting rare earth elements with smaller ion radius, to promote sintering of the side edges, and adding more rare earth elements to the capacitor section to control the sintering progress, ensuring that the difference between the two is suppressed , thereby improving overall reliability.
It effectively promotes the sintering of the side edges, reduces the difference in sintering progress between the capacitor part and the side edges, improves the reliability and moisture resistance of ceramic electronic components, and extends the life.
Smart Images

Figure CN113327768B_ABST
Abstract
Description
Field of the Invention
[0001] Certain aspects of the present invention relate to ceramic electronic components and methods of making the same. Background Art
[0002] Ceramic electronic devices such as stacked ceramic capacitors have a capacitor portion in which an internal electrode layer is stacked through a dielectric layer and a side edge protection side portion of the internal electrode layer (for example, see Japanese Patent Application Publication No. 2012-209539). For example, a common rare earth element is added to the capacitor portion and the side edge. Therefore, due to the addition of rare earth elements, the uneven distribution of each element in the sintering process is suppressed, and the reliability is improved (for example, see Japanese Patent Application Publication No. 2017-011172). Summary of the invention
[0003] Yet, in the ceramic electronic device with large stacking density, the sintering speed in the capacitor portion is larger than the sintering speed in the side edge.For example, this is because the removal of adhesive in the capacitor portion is delayed, and in the sintering process, the atmosphere in the capacitor portion is stronger than the reducibility in the side edge.When the sintering of the side edge is delayed, the densification of the side edge can not be promoted.Therefore, the reliability such as life characteristics or the moisture resistance under high temperature can decline.
[0004] An object of the present invention is to provide a ceramic electronic component capable of improving reliability and a method for manufacturing the same.
[0005] According to a first aspect of an embodiment, a ceramic electronic component is provided, comprising: a stacked structure having a substantially rectangular parallelepiped shape and comprising alternately stacked dielectric layers and internal electrode layers, the dielectric layers being mainly composed of ceramic, the internal electrode layers being alternately exposed at two end faces of the stacked chip that are opposite to each other, wherein the ion radius of a first rare earth element at a side edge is smaller than the ion radius of a first rare earth element at a capacitor portion, wherein the first rare earth element at the side edge is the rare earth element when only one rare earth element is added to the side edge, or the rare earth element with the largest amount when multiple rare earth elements are added to the side edge, wherein the first rare earth element at the capacitor portion is the rare earth element when only one rare earth element is added to the capacitor portion, or the rare earth element with the largest amount when multiple rare earth elements are added to the capacitor portion, wherein the side edge is a portion of an edge portion that covers the internal electrode layer and extends toward two side faces other than the two end faces, and wherein the capacitor portion is a portion of the internal electrode layers that are opposite to each other and are exposed at different end faces of the stacked structure.
[0006] According to a second aspect of the embodiment, a method for manufacturing a ceramic electronic component is provided, the method comprising: preparing a ceramic stacking structure, the ceramic stacking structure comprising a stacking portion and a side edge portion, the stacking portion having the following structure: a sheet material including particles whose main component is ceramic and a metal conductive paste pattern are alternately stacked so that the metal conductive paste is alternately exposed at two end surfaces of the stacking portion, and the side edge portion is arranged on two side surfaces of the stacking portion; and firing the ceramic stacking structure, wherein the ion radius of the first rare earth element of the side edge portion is smaller than the ion radius of the first rare earth element of the stacking portion, wherein the first rare earth element of the side edge portion is the rare earth element when only one rare earth element is added to the side edge portion, or the rare earth element with the largest amount when multiple rare earth elements are added to the side edge portion, wherein the first rare earth element of the stacking portion is the rare earth element when only one rare earth element is added to the stacking portion, or the rare earth element with the largest amount when multiple rare earth elements are added to the stacking portion. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 is a partial cross-sectional perspective view of a stacked ceramic capacitor;
[0008] Figure 2 is along Figure 1 A cross-sectional view taken along line AA;
[0009] Figure 3 is along Figure 1 A cross-sectional view taken along line BB;
[0010] Figure 4A This is an enlarged cross-sectional view of the side edge. Figure 4B is an enlarged view of the cross section of the end edge;
[0011] Figure 5 shows the concentration of rare earth elements in the capacitor portion and the side edge portion;
[0012] Figure 6 shows the concentration of rare earth elements in the capacitor portion and the side edge portion;
[0013] Figure 7 shows the concentration of rare earth elements in the capacitor portion and the side edge portion;
[0014] Figure 8 This is a flow chart of a method for manufacturing a multilayer ceramic capacitor.
[0015] Fig.9A and Fig. 9B The lamination process is shown;
[0016] Fig.10 shows the lamination process; and
[0017] Fig.11 The lamination process is shown. DETAILED DESCRIPTION
[0018] Hereinafter, exemplary embodiments will be described with reference to the accompanying drawings.
[0019] [Exemplary Embodiments]
[0020] Figure 1 is a partial cross-sectional perspective view of a stacked ceramic capacitor 100 according to an exemplary embodiment. Figure 2 is along Figure 1 A cross-sectional view taken along line AA. Figure 3 is along Figure 1 The cross-sectional view taken along the BB line. Figures 1 to 3 As shown, the laminated ceramic capacitor 100 includes: a laminated chip 10 having a rectangular parallelepiped shape; and external electrodes 20a and 20b respectively arranged on two end faces (edge faces) of the laminated chip 10 that are opposite to each other. Among the four faces other than the two end faces of the laminated chip 10, the two faces other than the top face and the bottom face in the lamination direction are called side faces. Each of the external electrodes 20a and 20b extends to the top face and the bottom face and the two side faces in the lamination direction of the laminated chip 10. However, the external electrodes 20a and 20b are spaced apart from each other.
[0021] The laminated chip 10 has a structure designed to have dielectric layers 11 and internal electrode layers 12 alternately laminated. The dielectric layer 11 contains a ceramic material used as a dielectric material. The end edge of the internal electrode layer 12 is alternately exposed to the first end face of the laminated chip 10 and the second end face of the laminated chip 10 that is different from the first end face. The external electrode 20a is arranged on the first end face. The external electrode 20b is arranged on the second end face. Therefore, the internal electrode layer 12 is alternately electrically connected to the external electrode 20a and the external electrode 20b. Therefore, the laminated ceramic capacitor 100 has a structure in which a plurality of dielectric layers 11 are laminated with the internal electrode layer 12 sandwiched therebetween. In the laminated structure of the dielectric layer 11 and the internal electrode layer 12, the outermost layer in the lamination direction is the internal electrode layer 12, and the cover layer 13 covers the top and bottom surfaces of the laminated structure. The cover layer 13 is mainly composed of a ceramic material. For example, the main component of the cover layer 13 is the same as the main component of the dielectric layer 11.
[0022] For example, the stacked ceramic capacitor 100 may be 0.25 mm in length, 0.125 mm in width, and 0.125 mm in height. The stacked ceramic capacitor 100 may be 0.4 mm in length, 0.2 mm in width, and 0.2 mm in height. The stacked ceramic capacitor 100 may be 0.6 mm in length, 0.3 mm in width, and 0.3 mm in height. The stacked ceramic capacitor 100 may be 1.0 mm in length, 0.5 mm in width, and 0.5 mm in height. The stacked ceramic capacitor 100 may be 3.2 mm in length, 1.6 mm in width, and 1.6 mm in height. The stacked ceramic capacitor 100 may be 4.5 mm in length, 3.2 mm in width, and 2.5 mm in height. However, the size of the stacked ceramic capacitor 100 is not limited.
[0023] The internal electrode layer 12 is mainly composed of a base metal such as nickel (Ni), copper (Cu) or tin (Sn). The internal electrode layer 12 may be composed of a noble metal such as platinum (Pt), palladium (Pd), silver (Ag) or gold (Au) or an alloy including one or more of them. The dielectric layer 11 is mainly composed of a ceramic material having a perovskite structure represented by the general formula ABO3. The perovskite structure includes ABO having a non-stoichiometric composition. 3-α Examples of such ceramic materials include, but are not limited to, barium titanate (BaTiO3), calcium zirconate (CaZrO3), calcium titanate (CaTiO3), strontium titanate (SrTiO3), and BaTiO3 having a perovskite structure. 1-x-y Ca x Sr y Ti 1- z Zr z O3(0≤x≤1, 0≤y≤1, 0≤z≤1).
[0024] like Figure 2 As shown in FIG. 1 , the portion where the internal electrode layer 12 connected to the external electrode 20a faces the internal electrode layer 12 connected to the external electrode 20b is a portion that generates capacitance in the multilayer ceramic capacitor 100. Therefore, this region is referred to as a capacitor portion 14. That is, the capacitor portion 14 is a portion where two adjacent internal electrode layers 12 connected to different external electrodes face each other.
[0025] The portion where the internal electrode layers 12 connected to the external electrode 20a face each other without sandwiching the internal electrode layer 12 connected to the external electrode 20b is called the end margin 15. The portion where the internal electrode layers 12 connected to the external electrode 20b face each other without sandwiching the internal electrode layer 12 connected to the external electrode 20a is also the end margin 15. That is, the end margin 15 is the portion where the internal electrode layers 12 connected to one external electrode face each other without sandwiching the internal electrode layer 12 connected to the other external electrode. The end margin 15 is a region where no capacitance is generated.
[0026] like Figure 3 As shown, in the laminated chip 10, the portion from each of the two side surfaces of the laminated chip 10 to the internal electrode layer 12 is called a side edge 16. That is, the side edge 16 is a portion extending toward each side surface of the laminated structure and covering each edge of the laminated internal electrode layer 12.
[0027] Figure 4A 1 is an enlarged cross-sectional view of the side edge 16. The side edge 16 has a structure in which the dielectric layer 11 and the inverse pattern layer 17 are alternately stacked in the direction in which the dielectric layer 11 and the internal electrode layer 12 are stacked in the capacitor portion 14 (stacking direction). Figure 4A and Figure 4B In the figure, the hatching for indicating the cross section is omitted. Each dielectric layer 11 in the capacitor portion 14 and the dielectric layer 11 in the corresponding side edge 16 form a continuous layer. This structure reduces the level difference between the capacitor portion 14 and the side edge 16.
[0028] Figure 4B 1 is an enlarged cross-sectional view of the end edge 15. Compared with the side edge 16, in the end edge 15, every other internal electrode layer 12 of the stacked internal electrode layers 12 extends to the outer end surface of the end edge 15. In addition, in the layer where the internal electrode layer 12 extends to the outer end surface of the end edge 15, the reverse pattern layer 17 is not stacked. Each dielectric layer 11 in the capacitor part 14 and the dielectric layer 11 in the corresponding end edge 15 form a continuous layer. This structure reduces the level difference between the capacitor part 14 and the end edge 15.
[0029] Capacitor section 14 and side edge 16 are formed by sintering powder material. It can be considered that, when common rare earth elements are added to capacitor section 14 and side edge 16, due to the addition of rare earth elements, the uneven distribution of each element in the sintering process is suppressed, and the reliability of laminated ceramic capacitor 100 is greatly improved. However, in laminated ceramic capacitor 100 with large stacking density, the sintering speed in capacitor section 14 is larger than that in side edge 16. For example, this is because the removal of adhesive in capacitor section 14 is delayed, and in the sintering process, the atmosphere in capacitor section 14 is more reductive than that in side edge 16. When the sintering of side edge 16 is delayed, the densification of side edge 16 can not be promoted. Therefore, the reliability such as life characteristics or moisture resistance at high temperature can be reduced.
[0030] Therefore, a method of adding Si (silicon) or a glass component used as a sintering aid to the side edge 16 is considered. The sintering aid promotes the sintering of the side edge 16. However, in this method, due to the difference between the composition of the capacitor portion 14 and the composition of the side edge 16, diffusion occurs during the sintering process. When Si or a glass component used as a sintering aid diffuses into the capacitor portion 14, excessive grain growth or degradation of the dielectric constant may occur. In this case, the electrical characteristics of the stacked ceramic capacitor 100 will decrease.
[0031] Therefore, adding rare earth elements is considered. Rare earth elements are added to ensure the reliability of the laminated ceramic capacitor 100. Rare earth elements improve the reliability of the laminated ceramic capacitor 100. On the other hand, rare earth elements increase the sintering completion temperature and delay sintering. In the following description, the role of rare earth elements will be explained.
[0032] Figure 5 FIG. 1 shows a case where a common rare earth element is added to the capacitor portion 14 and the side edge 16 in order to obtain a uniform concentration distribution of the rare earth element. Figure 5 In FIG. 1 , the horizontal axis represents the distance from the side (periphery) of the stacked chip 10. That is, Figure 5 The abscissa represents the distance from the surface of the side edge 16 to the capacitor portion 14. The interface between the side edge 16 and the capacitor portion 14 is approximately 30 μm. Figure 5 The ordinate represents the concentration of the rare earth element and shows the value when the maximum concentration of the rare earth element in the capacitor portion 14 and the side edge 16 is 100%. Figure 5 As shown, the concentration distribution of the rare earth element is uniform in the capacitor portion 14 and the side edge 16. Therefore, the concentration of the rare earth element is 100% at any position. In this structure, as described above, when the atmosphere in the capacitor portion 14 is more reductive than that in the side edge 16 during the sintering process, the densification of the side edge 16 is delayed and the reliability is reduced.
[0033] Therefore, if Figure 6As shown in FIG. 1 , it is considered to increase the amount of rare earth elements added to the capacitor portion 14 and reduce the amount of rare earth elements added to the side edge 16. Figure 6 In the case of , the amount of rare earth elements in the capacitor portion 14 is large. Also, near the interface between the capacitor portion 14 and the side edge 16, the amount of rare earth elements gradually decreases from the capacitor portion 14 to the side edge 16. Also, the amount of rare earth elements further decreases to the outside of the side edge 16. In this structure, sintering of the side edge 16 is suppressed. However, the amount of rare earth elements in the side edge 16 is small. Therefore, the reliability of the stacked ceramic capacitor 100 is reduced.
[0034] Therefore, in the embodiment, the ionic radius of the rare earth element is specified. When the ionic radius of the rare earth element is small, since the ionic radius of the B position is relatively small, the amount of the rare earth element dissolved in the B position becomes larger. When the ionic radius of the rare earth element is large, since the ionic radius of the A position is relatively large, the amount of the rare earth element dissolved in the A position becomes larger. In ABO3 having a perovskite structure, due to the crystal structure of ABO3, the diffusion rate of the A position is greater than the diffusion rate of the B position. Therefore, when a rare earth element with a small ionic radius is added, sintering is promoted.
[0035] When multiple types of rare earth elements are added to capacitor section 14, the rare earth element with the largest amount among the rare earth elements is called the first rare earth element of capacitor section 14. When one type of rare earth element is added to capacitor section 14, the rare earth element is the first rare earth element of capacitor section 14.
[0036] When multiple types of rare earth elements are added to the side edge 16, the rare earth element with the largest amount among the rare earth elements is called the first rare earth element of the side edge 16. When one type of rare earth element is added to the side edge 16, the rare earth element is the first rare earth element of the side edge 16.
[0037] In an embodiment, the trivalent ion radius of the first rare earth element of the side edge 16 is smaller than the trivalent ion radius of the first rare earth element of the capacitor portion 14. Figure 7 As shown, the concentration of the first rare earth element of the capacitor portion 14 is large in the capacitor portion 14. Near the interface between the capacitor portion 14 and the side edge 16, the concentration of the first rare earth element of the capacitor portion 14 decreases from the capacitor portion 14 to the side edge 16, and further decreases to the outside of the side edge 16. The concentration of the first rare earth element of the side edge 16 is large in the side edge 16. Near the interface between the capacitor portion 14 and the side edge 16, the concentration of the first rare earth element of the side edge 16 decreases from the side edge 16 to the capacitor portion 14, and further decreases to the inside of the capacitor portion 14. Therefore, the sintering of the side edge 16 is promoted. The difference between the sintering progress of the capacitor portion 14 and the sintering progress of the side edge 16 is suppressed. And, the effect of improving reliability by adding rare earth elements is improved.
[0038] As rare earth elements, La (lanthanum), Ce (cerium), Pr (praseodymium), Nd (neodymium), Pm (promethium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Y (yttrium), Er (erbium), Tm (thulium), Yb (ytterbium), Lu (lutetium), Sc (scandium) and the like can be used. Table 1 shows the trivalent, hexacoordinated ionic radii of the rare earth elements. The source of Table 1 is "RD Shannon, Acta Crystallogr., A32, 751 (1976)".
[0039] [Table 1]
[0040]
[0041] From the viewpoint of suppressing the difference between the sintering progress of the capacitor 14 and the sintering progress of the side edge 16, preferably, the difference between the trivalent ion radius of the first rare earth element of the capacitor 14 and the trivalent ion radius of the first rare earth element of the side edge 16 is large. For example, preferably, the ratio (trivalent ion radius of the first rare earth element of the capacitor 14): (trivalent ion radius of the first rare earth element of the side edge 16) is 1:0.999 or less. More preferably, the ratio is 1:0.993 or less.
[0042] In the case where the amount of the rare earth element in the side edge 16 is too large, the densification of the side edge 16 may be prevented, and the moisture resistance may be reduced. Therefore, preferably, the amount of the first rare earth element in the side edge 16 has an upper limit. For example, preferably, the ratio of the amount of the first rare earth element in the side edge 16 relative to the amount of the B-site element (for example, Ti in the case of barium titanate) is 0.05 or less. More preferably, the ratio is 0.03 or less. More preferably, the ratio is 0.015 or less.
[0043] On the other hand, from the viewpoint of improving the reliability caused by the rare earth element in the side edge 16, preferably, the amount of the first rare earth element in the side edge 16 has a lower limit. For example, in the side edge 16, preferably, the ratio of the amount of the first rare earth element to the amount of the B-site element is 0.001 or more. More preferably, the ratio is 0.005 or more. More preferably, the ratio is 0.0095 or more.
[0044] Preferably, the concentration of the first rare earth element in the side edge 16 as a whole is close to the concentration of the first rare earth element in the capacitor portion 14 as a whole. For example, in an embodiment, preferably, the ratio of the concentration of the first rare earth element in the side edge 16 as a whole to the concentration of the first rare earth element in the capacitor portion 14 as a whole is 0.5:1.0 to 1.0:0.5. More preferably, the ratio is 0.8:1.0 to 1.0:0.8. More preferably, the ratio is 0.95:1.0 to 1.0:0.95.
[0045] When the amount of the first rare earth element of the capacitor section 14 is too large, the dielectric constant of the capacitor section 14 may decrease. Therefore, preferably, the amount of the first rare earth element of the capacitor section 14 has an upper limit. For example, preferably, the ratio of the amount of the first rare earth element in the capacitor section 14 to the amount of the B-site element is less than 0.05. More preferably, the ratio is less than 0.03. More preferably, the ratio is less than 0.015. On the other hand, when the amount of the first rare earth element of the capacitor section 14 is too small, sufficient life improvement may not be achieved. Therefore, preferably, the amount of the first rare earth element of the capacitor section 14 has a lower limit. For example, in the capacitor section 14, preferably, the ratio of the amount of the first rare earth element to the amount of the B-site element is more than 0.001. More preferably, the ratio is more than 0.005. More preferably, the ratio is more than 0.0095.
[0046] When the main component ceramic of the capacitor part 14 and the side edge 16 is barium titanate, preferably, the first rare earth element of the capacitor part 14 is, for example, Dy, Ho, etc., and the first rare earth element of the side edge 16 is, for example, Er, Yb, Lu, etc. The first rare earth element of the capacitor part 14 can be Eu. The first rare earth element of the side edge 16 can be Tb, Dy, Ho, Y, Er, Yb or Lu. In this case, the sintering characteristics of the side edge 16 can be improved. And, the side edge 16 can be densified without increasing the sintering temperature. Therefore, the grain size of the side edge 16 can be very small. And the side edge 16 can be densified. Through this structure, the number of grain boundaries is large. Moreover, the resistance of the side edge 16 can be increased, and the increased resistance is maintained. Moreover, moisture can be prevented from intruding from the outside.
[0047] The removal of the binder in the capacitor section 14 may be delayed more than that in the cover layer 13. In this case, the atmosphere in the capacitor section 14 may be more reducing than that in the cover layer 13. Therefore, the sintering speed of the capacitor section 14 is greater than that of the cover layer 13. In this case, the sintering and densification of the cover layer 13 are not promoted. And reliability such as life characteristics or moisture resistance at high temperatures may be reduced.
[0048] Therefore, preferably, the trivalent ion radius of the rare earth element (the first rare earth element of the covering layer 13) with the largest amount among the rare earth elements in the covering layer 13 is smaller than the trivalent ion radius of the first rare earth element of the capacitor portion 14. In this case, the sintering of the covering layer 13 is promoted. The difference between the sintering progress of the capacitor portion 14 and the sintering progress of the covering layer 13 is suppressed. Moreover, the effect of improving reliability due to the addition of rare earth elements can be improved.
[0049] From the viewpoint of suppressing the difference between the sintering progress of the capacitor 14 and the sintering progress of the cover layer 13, preferably, the difference between the trivalent ion radius of the first rare earth element of the capacitor 14 and the trivalent ion radius of the first rare earth element of the cover layer 13 is large. For example, preferably, the ratio (trivalent ion radius of the first rare earth element of the capacitor 14): (trivalent ion radius of the first rare earth element of the cover layer 13) is 1:0.999 or less. More preferably, the ratio is 1:0.993 or less.
[0050] When the amount of the rare earth element in the cover layer 13 is too large, the densification of the cover layer 13 may be prevented, and the moisture resistance may be reduced. Therefore, preferably, the amount of the first rare earth element in the cover layer 13 has an upper limit. For example, in the cover layer 13, preferably, the ratio of the amount of the first rare earth element to the amount of the B-site element (for example, Ti in the case of barium titanate) is 0.05 or less. More preferably, the ratio is 0.03 or less. More preferably, the ratio is 0.015 or less.
[0051] On the other hand, from the viewpoint of improving the reliability due to the rare earth element in the cover layer 13, preferably, the amount of the first rare earth element in the cover layer 13 has a lower limit. For example, in the cover layer 13, preferably, the ratio of the amount of the first rare earth element to the amount of the B-site element is 0.001 or more. More preferably, the ratio is 0.005 or more. More preferably, the ratio is 0.0095 or more.
[0052] The ratio of the concentration of the first rare earth element in the entire cover layer 13 to the concentration of the first rare earth element in the entire capacitor 14 is preferably 0.5:1.0 to 1.0:0.5. More preferably, the ratio is 0.8:1.0 to 1.0:0.8. More preferably, the ratio is 0.95:1.0 to 1.0:0.95.
[0053] When the main component ceramics of the capacitor part 14 and the cover layer 13 are barium titanate, preferably, the first rare earth element of the capacitor part 14 is, for example, Dy, Ho, etc., and the first rare earth element of the cover layer 13 is, for example, Er, Yb, Lu, etc. The first rare earth element of the capacitor part 14 can be Eu. The first rare earth element of the cover layer 13 can be Tb, Dy, Ho, Y, Er, Yb or Lu. In this case, the sintering characteristics of the cover layer 13 can be improved. Moreover, the cover layer 13 can be densified without increasing the sintering temperature. Therefore, the grain size of the cover layer 13 can be very small. And the cover layer 13 can be densified. Through this structure, the number of grain boundaries is very large. And the resistance of the cover layer 13 can be increased, and the increased resistance can be maintained. And moisture can be prevented from invading from the outside.
[0054] Next, a method for manufacturing the multilayer ceramic capacitor 100 will be described. Figure 8 1 is a flowchart of a method for manufacturing the multilayer ceramic capacitor 100 .
[0055] [Manufacturing raw material powder (S1)]
[0056] A dielectric material for forming the dielectric layer 11 is prepared. The dielectric material includes a ceramic which is the main component of the dielectric layer 11. The A-site element and the B-site element contained in the dielectric layer 11 are generally contained in the dielectric layer 11 in the form of a sintered compact of ABO3 particles. For example, BaTiO3 is a tetragonal compound having a perovskite structure and exhibiting a high dielectric constant. Generally, the BaTiO3 is obtained by reacting a titanium raw material such as titanium dioxide with a barium raw material such as barium carbonate to synthesize barium titanate. As a method for synthesizing ceramics constituting the dielectric layer 11, many methods are known. For example, a solid phase method, a sol-gel method, a hydrothermal method, etc. are known. This embodiment may use any of these methods.
[0057] Depending on the purpose, an additive compound may be added to the obtained ceramic powder. The additive compound may be an oxide of zirconium (Zr), calcium (Ca), strontium (Sr), magnesium (Mg), manganese (Mn), vanadium (V), chromium (Cr) or a rare earth element, or an oxide of cobalt (Co), Ni, lithium (Li), B (boron), sodium (Na), potassium (K) or Si, or a glass
[0058] Next, an edge material for forming the end edge 15 and the side edge 16 is prepared. The edge material includes a main component ceramic of the end edge 15 and the side edge 16. BaTiO3 powder is manufactured as the main component ceramic. The BaTiO3 powder can be manufactured in the same method as the dielectric material. Depending on the purpose, an additive compound is added to the barium titanate ceramic powder obtained by the same method as the manufacturing method of the above-mentioned dielectric material. The additive compound can be an oxide of Zr, Ca, Sr, Mg, Mn, V, Cr or a rare earth element, an oxide of Co, Ni, Li, B, Na, K or Si, or glass.
[0059] Next, a covering material for forming the covering layer 13 is prepared. The covering material includes a main component ceramic of the covering material. BaTiO3 powder is manufactured as the main component ceramic. The BaTiO3 powder can be prepared by the same method as the dielectric material. Depending on the purpose, an additive compound is added to the barium titanate ceramic powder obtained by the same method as the manufacturing method of the above-mentioned dielectric material. The additive compound can be an oxide of Zr, Ca, Sr, Mg, Mn, V, Cr or a rare earth element, an oxide of Co, Ni, Li, B, Na, K or Si, or glass. As the covering material, the above-mentioned edge material can be used.
[0060] [Lamination Step (S2)]
[0061] Next, a binder such as polyvinyl butyral (PVB) resin, an organic solvent such as ethanol or toluene, and a plasticizer are added to the obtained dielectric material and wet mixed. Using the obtained slurry, a strip-shaped dielectric green sheet 51 having a thickness of, for example, 0.8 μm or less is applied to a substrate by, for example, a die coater method or a doctor blade method, and then dried.
[0062] Next, if Fig.9A As shown, a metal conductive paste for forming an internal electrode is printed by screen printing or gravure printing to form a first pattern 52 of an internal electrode layer on the surface of a dielectric green sheet 51. The metal conductive paste for forming an internal electrode contains an organic binder. Ceramic particles are added to the metal conductive paste as a co-material. The main component of the ceramic particles is not specifically limited, but is preferably the same as the main component ceramic of the dielectric layer 11.
[0063] Next, a binder such as an ethyl cellulose-based binder and an organic solvent such as a terpineol-based solvent are added to the edge material and kneaded to obtain an edge paste for the reverse pattern layer 17. Fig.9A As shown, the second pattern 53 is formed by printing an edge paste in a peripheral area on the dielectric green sheet 51 where the first pattern 52 is not printed, so that the second pattern 53 and the first pattern 52 form a flat surface.
[0064] Thereafter, a predetermined number of stacking units (dielectric green sheets 51, first patterns 52, and second patterns 53) are stacked while peeling off the substrate, so that the internal electrode layers 12 and the dielectric layers 11 are alternately exposed to both end surfaces in the length direction of the dielectric layer 11, so as to be alternately led to a pair of external electrodes with different polarities, such as Fig. 9B For example, 100 to 500 stacking units are stacked.
[0065] Next, a binder such as polyvinyl butyral (PVB) resin, an organic solvent such as ethanol or toluene, and a plasticizer are added to the resulting covering material and wet mixed. Using the resulting slurry, a covering sheet 54 having a thickness of, for example, 10 μm or less is applied to the substrate by, for example, a die coater method or a doctor blade method, and then dried. Fig.10As shown, a predetermined number (e.g., 2 to 10) of cover sheets 54 are stacked above and below the stacked dielectric green sheets 51. Thereafter, the stacked structure is cramped. The resulting stacked structure is punched into a predetermined size (e.g., 1.0 mm×0.5 mm). A metal conductive paste for external electrodes 20a and 20b is applied to both end surfaces of the resulting stacked structure by dip coating. Then, the metal conductive paste is dried. Thus, a ceramic stacked structure is obtained. Instead of this method, a predetermined number of cover sheets 54 may be stacked and cramped. Thereafter, the stacked cover sheets 54 may be fixed above and below the stacked dielectric green sheets 51.
[0066] exist FIG. 9A to FIG. 10 In the process of forming the dielectric green sheet 51, the portion where the first pattern 52 is laminated with the portion of the dielectric green sheet 51 corresponding to the first pattern 52 is an example of a laminated portion where a sheet of BaTiO3 particles, the main component ceramic, and a pattern of a metal conductive paste are alternately laminated. The portion where the second pattern 53 is laminated with the portion of the dielectric green sheet 51 other than the first pattern 52 is an example of a side edge portion arranged on a wide face of the laminated portion.
[0067] The side edge portion may be fixed to the side of the laminated portion, or may be printed on the side of the laminated portion. Figure 1 As shown, dielectric green sheets 51 and first patterns having the same width as dielectric green sheets 51 are alternately stacked. Thus, a stacked portion is formed. Next, a sheet formed of a side edge paste is fixed to the side of the stacked portion. Alternatively, the side edge paste is printed on the side of the stacked portion. Thus, a side edge portion can be formed. The edge paste can be used as a side edge paste. The portion where the side edge paste is formed on the side of the stacked portion where the dielectric green sheets 51 and the first pattern 52 are stacked corresponds to the side edge portion.
[0068] exist FIG. 9A to FIG. 11 In the process of manufacturing the raw material, the amount of the additive is adjusted in the raw material manufacturing process so that the trivalent ion radius of the first rare earth element of the side edge 16 is smaller than the trivalent ion radius of the first rare earth element of the capacitor portion 14. Moreover, preferably, the amount of the additive is adjusted in the raw material manufacturing process so that the trivalent ion radius of the first rare earth element of the cover layer 13 is smaller than the trivalent ion radius of the first rare earth element of the capacitor portion 14.
[0069] [Firing step (S3)]
[0070] The binder was removed from the obtained ceramic laminated structure in an N2 atmosphere. Thereafter, Ni paste to be used as the base layer of the external electrodes 20a and 20b was printed. The ceramic laminated structure was heated to 100°C and 1300°C at an oxygen partial pressure of 10 -5 Up to 10-8 The obtained ceramic laminate structure is fired in a reducing atmosphere of 0.5 atm for 10 minutes to 2 hours. Thus, the laminated ceramic capacitor 100 is obtained.
[0071] [Reoxidation step (S4)]
[0072] Thereafter, a reoxidation process is performed in a N2 gas atmosphere at a temperature range of 600°C to 1000°C.
[0073] [Plating step (S5)]
[0074] Thereafter, a metal layer such as Cu, Ni, Sn, or the like may be formed on the external electrodes 20 a and 20 b by plating.
[0075] In the manufacturing method of the embodiment, the sintering of the side edge 16 is promoted. The difference between the sintering progress of the capacitor portion 14 and the sintering progress of the side edge 16 is reduced. Moreover, the improvement in reliability due to the addition of rare earth elements is improved. The sintering of the cover layer 13 is promoted. The difference between the sintering progress of the capacitor portion 14 and the sintering progress of the cover layer 13 is reduced. Moreover, the improvement in reliability due to the addition of rare earth elements is improved.
[0076] In the above embodiments, the stacked ceramic capacitor is described as an example of a ceramic electronic component. However, the embodiments are not limited to the stacked ceramic capacitor. For example, the ceramic electronic component may be other electronic components such as a varistor or a thermistor.
[0077] [Example]
[0078] The difference in sintering densification temperature caused by the difference in ionic radius was confirmed.
[0079] Additives are added to barium titanate powder. The obtained barium titanate powder is wet mixed and crushed in a ball mill. Thus, a dielectric material is obtained. Additives are added to barium titanate powder. The obtained barium titanate powder is wet mixed and crushed in a ball mill. Thus, an edge material is obtained. Additives are added to barium titanate powder. The obtained barium titanate powder is wet mixed and crushed in a ball mill. Thus, a covering material is obtained.
[0080] A butyral material used as an organic binder, ethanol and toluene used as a solvent are mixed with a dielectric material. A dielectric green sheet 51 is manufactured by a doctor blade method. A first pattern 52 is printed on the dielectric green sheet 51. 500 dielectric green sheets 51 on which the first pattern 52 is printed are stacked so that each first pattern 52 is shifted alternately. A butyral material used as an organic binder, ethanol and toluene used as a solvent are mixed with a covering material. A covering sheet 54 is manufactured by a doctor blade method. Thereafter, the covering sheet 54 is stacked on the stacked dielectric green sheet 51. Another covering sheet 54 is stacked under the stacked dielectric green sheet 51. The stacked structure is pressed. Thus, a ceramic stacked structure is obtained.
[0081] The ceramic laminate structure is cut so that the cover sheet 54, the dielectric green sheet 51 and the first pattern 52 have the same width. Then, an ethyl cellulose material used as an organic binder and a terpineol material used as a solvent are mixed with the edge material. The obtained edge material is kneaded with a roll mill. Thus, a side edge paste is prepared. A sheet made of the side edge slurry is fixed to both sides of the cut ceramic laminate structure. Then, the obtained ceramic laminate structure is fired in a reducing atmosphere at 1200°C.
[0082] For various rare earth elements added as additives, repeat the same process to make chip samples. The number of holes in the central part of the side edge 16 of each chip sample is quantified by SEM (scanning electron microscope). The sample chip is polished until the central part is exposed. The cross section of the central part is observed by SEM. By using image processing software ImageJ, the area of the side edge 16 and the area of the hole in the side edge 16 are measured. The ratio of the area of the residual holes relative to the area of the side edge 16 is the ratio of the residual holes. Each ratio is used to compare the rare earth elements.
[0083] It can be determined that the lower the ratio of the residual pores in the central portion of the side edge 16 is, the more the sintering is progressing. When the densification progresses at the same sintering temperature, when determining the sintering temperature, it is determined that the sintering temperature is reduced. When the densification is delayed at the same sintering temperature, it is determined that the sintering temperature is increased.
[0084] Tables 2, 3, 4 and 5 show the results. In Table 2, it is confirmed whether the sintering densification temperature is higher or lower than the sintering densification temperature in the case of adding Ho. As shown in Table 2, when a rare earth element having an ionic radius larger than Ho is added, the sintering densification temperature is high. On the other hand, when a rare earth element having an ionic radius smaller than Ho is added, the sintering densification temperature is low. In Table 2, the ratio of the ionic radius of each rare earth element to the ionic radius of Ho is shown.
[0085] [Table 2]
[0086]
[0087]
[0088] In Table 3, it is confirmed whether the sintering densification temperature is higher or lower than the sintering densification temperature in the case of adding Dy. As shown in Table 3, when a rare earth element having an ionic radius larger than Dy is added, the sintering densification temperature is high. On the other hand, when a rare earth element having an ionic radius smaller than Dy is added, the sintering densification temperature is low. In Table 3, the ratio of the ionic radius of each rare earth element to the ionic radius of Dy is shown.
[0089] [Table 3]
[0090]
[0091] [Table 4]
[0092]
[0093]
[0094] [Table 5]
[0095]
[0096] In Table 4, it is confirmed whether the sintering densification temperature is higher or lower than the sintering densification temperature in the case of adding Eu. As shown in Table 4, when a rare earth element with an ionic radius larger than Eu is added, the sintering densification temperature is high. On the other hand, when a rare earth element with an ionic radius smaller than Eu is added, the sintering densification temperature is low. In Table 4, the ratio of the ionic radius of each rare earth element to the ionic radius of Eu is shown.
[0097] In Table 5, it is confirmed whether the sintering densification temperature is higher or lower than the sintering densification temperature in the case of adding La. As shown in Table 5, when a rare earth element having an ionic radius larger than La is added, the sintering densification temperature is high. On the other hand, when a rare earth element having an ionic radius smaller than La is added, the sintering densification temperature is low. In Table 5, the ratio of the ionic radius of each rare earth element to the ionic radius of La is shown.
[0098] According to the results of Table 2, Table 3, Table 4 and Table 5, when a rare earth element with a small ionic radius is added, the sintering densification temperature becomes lower. When a rare earth element with a large ionic radius is added, the sintering densification temperature becomes higher. When the sintering densification temperature is low, sintering is promoted. When the sintering densification temperature is high, sintering is delayed.
[0099] Next, samples of the laminated ceramic capacitor were manufactured and the characteristics of the samples were measured.
[0100] (Example) Additives are added to barium titanate powder. The obtained barium titanate powder is wet mixed and crushed in a ball mill. Thus, a dielectric material is obtained. Additives are added to barium titanate powder. The obtained barium titanate powder is wet mixed and crushed in a ball mill. Thus, an edge material is obtained. Additives are added to barium titanate powder. The obtained barium titanate powder is wet mixed and crushed in a ball mill. Thus, a covering material is obtained.
[0101] A butyral material used as an organic binder, ethanol and toluene used as a solvent are mixed with a dielectric material. A dielectric green sheet 51 is manufactured by a doctor blade method. A first pattern 52 is printed on the dielectric green sheet 51. 500 dielectric green sheets 51 on which the first pattern 52 is printed are stacked so that each first pattern 52 is shifted alternately. A butyral material used as an organic binder, ethanol and toluene used as a solvent are mixed with a covering material. A covering sheet 54 is manufactured by a doctor blade method. Thereafter, the covering sheet 54 is stacked on the stacked dielectric green sheet 51. Another covering sheet 54 is stacked under the stacked dielectric green sheet 51. The stacked structure is pressed. Thus, a ceramic stacked structure is obtained.
[0102] The ceramic laminate structure is cut so that the cover sheet 54, the dielectric green sheet 51 and the first pattern 52 have the same width. Then, an ethyl cellulose material used as an organic binder and a terpineol material used as a solvent are mixed with the edge material. The obtained edge material is kneaded by a roller mill. Thus, a side edge paste is prepared. A sheet made of the side edge slurry is fixed to both sides of the cut ceramic laminate structure. Then, the obtained ceramic laminate structure is fired.
[0103] In the embodiment, Ho is added to the dielectric material and Yb is added to the edge material so that (ion radius of the first rare earth element of the side edge 16) / (ion radius of the first rare earth element of the capacitor 14) is 0.96.
[0104] (Comparative Example 1) In Comparative Example 1, Ho was added to the dielectric material and the edge material so that (ion radius of the first rare earth element of the side edge 16) / (ion radius of the first rare earth element of the capacitor 14) was 1. Other conditions were the same as those in Example 1.
[0105] (Comparative Example 2) In Comparative Example 2, no rare earth element is added to the edge material. Other conditions are the same as those in Example 1.
[0106] (Analysis of relative density) For the embodiment and comparative examples 1 and 2, the relative density of the central part of the side edge 16 is measured when the relative density without holes is 100%. In the measurement of relative density, the sample chip is polished until the central part is exposed. The cross section of the central part is observed by SEM. The area of the side edge and the area of the hole in the side edge are measured in the field of view. The ratio of the area of the hole to the area of the side edge is the relative density. The relative density is expressed by the following formula. Image processing software ImageJ was used.
[0107] Total area of hole / side edge area
[0108] (Life Characteristics) For the examples and comparative examples 1 and 2, a voltage of 8 V was applied to 100 samples at a temperature of 125° C. And, the time until 50% of the 100 samples were damaged was measured. Under this condition, when a current of 1 mA or more flowed, the sample was determined to be damaged.
[0109] (Moisture resistance at high temperature) For the embodiment and comparative examples 1 and 2, a voltage of 4 V was applied to 100 samples at a temperature of 85° C. and a relative humidity of 85%. The samples were kept under this condition for 17 hours. Thereafter, the DC resistance was measured by using an insulation resistance meter. When the DC resistance was 1 MΩ or less, the sample was determined to be defective. The number of samples determined to be defective was counted.
[0110] Table 6 shows the results. In Comparative Example 1, the relative density of the central part of the side edge 16 in the stacking direction is relatively low at 94.60%. It is believed that this is because a common rare earth element is added to the capacitor portion 14 and the side edge 16, and the densification of the side edge 16 is delayed. In Comparative Example 1, the moisture resistance at high temperature is reduced, and the reliability is reduced. It is believed that this is because the densification of the side edge 16 is delayed.
[0111] [Table 6]
[0112]
[0113] In Comparative Example 2, the relative density of the central portion of the side edge 16 in the stacking direction is high at 99.40%. It is believed that this is because no rare earth element is added to the side edge 16, and the densification of the side edge 16 is not delayed. However, the life characteristics are reduced and the reliability is reduced. It is believed that this is because no rare earth element is added to the side edge 16 to achieve the effect of improving reliability.
[0114] On the other hand, in the embodiment, the relative density of the central part of the side edge 16 in the stacking direction is high at 98.20%. The moisture resistance at high temperature is good. And the reliability is improved. It is believed that this is because the ion radius of the first rare earth element in the side edge 16 is smaller than the ion radius of the first rare earth element of the capacitor part 14, and the delay of the densification of the side edge 16 is suppressed. In this embodiment, the life characteristics are good. And the reliability is improved. It is believed that this is because the rare earth element that improves the reliability is added to the side edge.
[0115] From the above results, it was confirmed that the sintering of the side edge 16 was promoted because the trivalent ion radius of the first rare earth element of the side edge 16 was smaller than the trivalent ion radius of the first rare earth element of the capacitor portion 14. It was also confirmed that the difference between the sintering progress of the capacitor portion 14 and the sintering progress of the side edge 16 was suppressed, and the effect of improving reliability caused by adding the rare earth element was enhanced.
[0116] Although the embodiments of the present invention have been described in detail, it should be understood that the various changes, substitutions, and alterations could be made hereto without departing from the spirit and scope of the invention.
Claims
1. A ceramic electronic component, comprising: A laminate structure having a substantially rectangular parallelepiped shape and comprising alternately laminated dielectric layers and internal electrode layers, wherein the dielectric layers are mainly composed of ceramics and the internal electrode layers are alternately exposed at two end faces of the laminate structure that are opposite to each other, wherein the ion radius of the first rare earth element at the side edge is smaller than the ion radius of the first rare earth element at the capacitor portion, wherein the first rare earth element of the side edge is the rare earth element when only one rare earth element is added to the side edge, or the rare earth element with the largest amount when multiple rare earth elements are added to the side edge, wherein the first rare earth element of the capacitor section is the rare earth element when only one rare earth element is added to the capacitor section, or the rare earth element with the largest amount when multiple rare earth elements are added to the capacitor section, The side edge is a portion covering the edge portion of the internal electrode layer extending toward two side surfaces excluding two end surfaces, The capacitor portion is a portion where the internal electrode layers exposed at different end surfaces of the stacked structure face each other, and The ratio of the ion radius of the first rare earth element of the capacitor to the ion radius of the first rare earth element of the side edge is 1:0.987 or less. 2 . The ceramic electronic component according to claim 1 , wherein a ratio of an ion radius of the first rare earth element of the capacitor portion to an ion radius of the first rare earth element of the side edge is 1:0.96 or less. 3 . The ceramic electronic component according to claim 1 , wherein in the side edge, a ratio of an amount of the first rare earth element of the side edge to an amount of the B-site element of the side edge is 0.001 or more and 0.05 or less.
4. The ceramic electronic component according to claim 1 or 2, wherein the first rare earth element of the side edge is Er, Yb or Lu, The first rare earth element of the capacitor is Dy or Ho.
5. The ceramic electronic component according to claim 1 or 2, wherein the first rare earth element of the side edge is Tb, Dy, Ho, Y, Er, Yb or Lu, The first rare earth element of the capacitor is Eu. 6 . The ceramic electronic component according to claim 1 , wherein a main component ceramic of the dielectric layer is barium titanate.
7. The ceramic electronic component according to claim 1 or 2, further comprising: a cover layer provided on at least one of the top surface and the bottom surface in the stacking direction of the stacked structure, wherein the ion radius of the first rare earth element of the capping layer is smaller than the ion radius of the first rare earth element of the capacitor portion, and The first rare earth element of the capping layer is the rare earth element when only one rare earth element is added to the capping layer, or the rare earth element with the largest amount when multiple rare earth elements are added to the capping layer.
8. The ceramic electronic component according to claim 1 or 2, wherein the first rare earth element of the side edge is Y, The first rare earth element of the capacitor is Dy.
9. A method for manufacturing a ceramic electronic component, the method comprising: preparing a ceramic laminated structure, the ceramic laminated structure including a laminated portion and a side edge portion, the laminated portion having a structure in which sheets including particles whose main component is ceramic and metal conductive paste patterns are alternately laminated so that the metal conductive paste is alternately exposed at both end surfaces of the laminated portion, and the side edge portion is provided on both side surfaces of the laminated portion; and firing the ceramic laminate structure, After firing, the metal conductive paste forms an internal electrode layer, and the portions of the internal electrode layers exposed at different end surfaces of the stacked portion facing each other form a capacitor portion. wherein the ion radius of the first rare earth element of the side edge portion is smaller than the ion radius of the first rare earth element of the stacked portion, wherein the first rare earth element of the side edge portion is the rare earth element when only one rare earth element is added to the side edge portion, or the rare earth element with the largest amount when multiple rare earth elements are added to the side edge portion, wherein the first rare earth element of the laminated portion is the rare earth element when only one rare earth element is added to the laminated portion, or the rare earth element with the largest amount when multiple rare earth elements are added to the laminated portion, and The ratio of the ion radius of the first rare earth element of the capacitor portion to the ion radius of the first rare earth element of the side edge portion is 1:0.987 or less.